2011
DOI: 10.1080/07347332.2011.616574
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life of Patients Undergoing Surgical Treatment for Newly-Diagnosed, Clinically Localized Renal Cell Carcinoma

Abstract: This investigation sought to evaluate the psychological needs of individuals (N = 28) undergoing nephrectomy for newly diagnosed, localized renal cell carcinoma (RCC) using a mixed qualitative-quantitative approach. The qualitative component consisted of individual semi-structured interviews ≥4 weeks postnephrectomy. The quantitative component involved standardized measures assessing anxiety, depressive symptoms, psychological distress, and general and disease specific quality of life (QOL) prior to nephrectom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
14
0
2
Order By: Relevance
“…With this in mind, a logical interpretation of our results is that the QoL metrics that are important for patients with RCC, and those that could be modulated by the type of surgery are not disease specific. Further supporting this notion is our own previous observation that RCC patients do not express a high level of concern regarding their cancer following surgical excision of the tumor [4]. Indeed, attitudes expressed in the focus groups for our previous study indicated a low level of concern regarding the risk of cancer recurrence following surgery.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…With this in mind, a logical interpretation of our results is that the QoL metrics that are important for patients with RCC, and those that could be modulated by the type of surgery are not disease specific. Further supporting this notion is our own previous observation that RCC patients do not express a high level of concern regarding their cancer following surgical excision of the tumor [4]. Indeed, attitudes expressed in the focus groups for our previous study indicated a low level of concern regarding the risk of cancer recurrence following surgery.…”
Section: Discussionsupporting
confidence: 58%
“…To date, a handful of investigators have addressed the question of QoL outcomes in RCC patients [4][5][6][7][8][9][10]; however only three have directly addressed the direct comparison of QoL measures between patients undergoing NSS and RN [5,6,8]. Interestingly, while one study reported no difference in QoL-related outcomes between the two surgical groups [5], two of the studies presented evidence suggesting improved QoL outcomes for the NSS versus RN group [6,8].…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…To date, a handful of investigators have addressed the question of QoL outcomes in RCC patients [4-10]; however only three have directly addressed the direct comparison of QoL measures between patients undergoing NSS and RN [5,6,8]. Interestingly, while one study reported no difference in QoL-related outcomes between the two surgical groups [5], two of the studies presented evidence suggesting improved QoL outcomes for the NSS versus RN group [6,8].…”
Section: Introductionmentioning
confidence: 99%